Longitudinal relationship between posttraumatic cognitions and internalising symptoms in children and adolescents - Anke de Haan; Kristian Kleinke; Eve Degen; Markus A. Landolt (European Journal of Psychotraumatology, 2024)
Background: Little is known about the naturalistic course of posttraumatic cognitions (PTCs) after exposure to a potentially traumatic event (PTE) in children and adolescents. Moreover, previous studies on the longitudinal associations of PTCs with internalising symptoms yielded mixed results.Objective: To explore the naturalistic courses and longitudinal associations of dysfunctional PTCs and functional PTCs with posttraumatic stress symptoms (PTSS), depression, and anxiety.Method: A total of 115 children and adolescents, aged 7–15 years, were assessed within 1 month, 3 months, and 6 months after exposure to an acute accidental PTE. Repeated measures analyses of variance were conducted to capture the naturalistic courses of PTCs and internalising symptoms. Cross-lagged panel analyses were applied to explore the longitudinal relationship between dysfunctional and functional PTCs, along with their longitudinal associations with PTSS, depression, and anxiety.Results: Dysfunctional PTCs and internalising symptoms decreased, whereas functional PTCs increased over time. Dysfunctional and functional PTCs were moderately inversely related, but no significant cross-lagged paths emerged among them. Dysfunctional PTCs were moderately to strongly associated with internalising symptoms, while functional PTCs were weakly to moderately inversely associated with internalising symptoms. Initial PTSS predicted later dysfunctional PTCs (β = .31, p < .05), but not vice versa.Conclusions: Dysfunctional PTCs, functional PTCs, and internalising symptoms were entangled over time. Our findings support the cognitive scar model with initial PTSS predicting later dysfunctional PTCs. Future research complementing between-subject with within-subject analyses could offer additional insights into the longitudinal relationship between dysfunctional PTCs, functional PTCs, and psychological symptoms.